2021
DOI: 10.3892/etm.2021.9675
|View full text |Cite
|
Sign up to set email alerts
|

COVID‑19 and its consequences on mental health (Review)

Abstract: As one year is approaching since the beginning of the Coronavirus disease 2019 (COVID-19) pandemic, it is important to acknowledge the detrimental effect that it is having on mental health at the individual, societal and public health levels. The current review presents the direct and indirect psychological impact of COVID-19 on the general public, as well as on vulnerable groups, including the elderly, the young, healthcare professionals, people with pre-existing mental health issues, those infected by COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
111
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 158 publications
(121 citation statements)
references
References 45 publications
3
111
2
5
Order By: Relevance
“…First and foremost, this pandemic has forced us to realise that medical education can become an extremely vulnerable asset in times of health crises and should not always be taken for granted in its traditional form, especially in the context of future COVID-19 waves and future pandemics. 97 In Singapore, medical educators were driven by the past H1N1 pandemic to prepare a contingency plan for similar future crises. 34 Creating a hybrid environment of fundamental traditional methods with novel technological tools could solidify the provision of medical education even in times in which its integrity is threatened.…”
Section: A 'Crash Test' For Education In the Future?mentioning
confidence: 99%
“…First and foremost, this pandemic has forced us to realise that medical education can become an extremely vulnerable asset in times of health crises and should not always be taken for granted in its traditional form, especially in the context of future COVID-19 waves and future pandemics. 97 In Singapore, medical educators were driven by the past H1N1 pandemic to prepare a contingency plan for similar future crises. 34 Creating a hybrid environment of fundamental traditional methods with novel technological tools could solidify the provision of medical education even in times in which its integrity is threatened.…”
Section: A 'Crash Test' For Education In the Future?mentioning
confidence: 99%
“…urban, rural, semi-rural settlement) on distress. Social support was measured using the Interview Schedule for Social Integration (ISSI) [49], which assesses social support in terms of the Availability and Adequacy of Social Interaction and Social Attachment.…”
Section: Independent Variablesmentioning
confidence: 99%
“…The authors encouraged preventative support and early intervention for children and adolescents to combat the increasing mental health issues. At the other end of the age spectrum, a number of studies have indicated that older adults are disproportionally affected by COVID-related mental health disorders, morbidity and mortality (Palmer et al, 2020;Zheng et al, 2020;Bae et al, 2021;Tsamakis et al, 2021).…”
Section: Introductionmentioning
confidence: 99%